Induced changes in the growth of four plant species due to lead toxicity - Adriana A. Batista; Jorge A. G. Santos; Marcela R. Bomfim; Flávia M. Moreira; Emylly F. Leal; Joseane N. da Conceição (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Lead is a toxic metal that affects plant growth and the ecosystem. This study evaluated the lead (Pb) bioaccumulation potential of vetiver (Vetiveria zizanioides L.), sunflower (Helianthus annuus L.), elephant ear (Alocasia macrorrhiza) and ‘embaúba’ (Cecropia sp.). The plant species were tested in a 50% nutrient solution - Hoagland and Arnon, constantly aerated, containing five Pb concentrations: 0, 50, 100, 200 and 400 mg L-1). The treatments were arranged in a completely randomized design in a 4 x 5 factorial scheme, with four replicates. The Pb contents in the plants increased linearly with the Pb exposure concentration. Vetiver was the species with the highest Pb content in the shoots (260.24 mg kg-1) and sunflower, in the roots (44925.20 mg kg-1). Pb concentration of up to 100 and 50.9 mg L-1 stimulated sunflower biomass and root length, respectively. None of the evaluated species met the hyperaccumulator criterion; however, sunflower and vetiver have the potential to be tested for phytostabilization purposes.